Evaluating the Efficiency of Lemna perpussilla in Removing Heavy Metals from River Wastewater in Yogyakarta - Riyadi, Fajar; Hasibuan, Selviany Br; Nababan, Jeremia Gusti; Avianto, Yovi (Universitas Islam Negeri Mataram, 2025)
Heavy metal pollution in Yogyakarta's rivers, caused by textile industries, sand mining, and domestic waste, poses significant environmental and health risks. While conventional water treatment methods face limitations, phytoremediation using Lemna offers a sustainable solution due to its ability to absorb heavy metals efficiently. This study assessed the impact of varying Lemna biomass (control, 20 g, 30 g, 40 g, 50 g per container) on reducing As, Cd, Cr, and Pb in textile, sand mining, and domestic wastewater over three weeks. Heavy metal concentrations were measured using an Atomic Absorption Spectrophotometer (AAS), and Lemna’s growth rates were analyzed using ANOVA followed by Tukey’s HSD. Results showed that Lemna perpusilla effectively adsorbs As, Cd, Cr, and Pb from domestic, sand mining, and batik textile wastewater, with higher biomass leading to improved removal efficiencies. Maximum heavy metal adsorption was observed in batik textile wastewater, achieving over 70% removal for all metals, while domestic and sand mining wastewater showed variable adsorption rates depending on the metal and Lemna biomass. Optimal biomass for growth and adsorption varied: 30 g for domestic, 50 g for sand mining, and 40 g for batik textile wastewater.